Monitoring and Analysis of the Current Environmental Situation of Electromagnetic Radiation from 5G Application Base Stations. Issue 1 (1st April 2022) - Gong, Yuan; Guo, Xiaoqi; Liu, Qiuxin; Long, Yifei; Li, Yangwei
Abstract: With the rapid development of the 5G era, the concern of human health risks caused by the construction of mobile base stations has also come to light. To understand the current situation of the electromagnetic radiation environment of 5G application base stations is the basis for avoiding the old road of "pollution before treatment" in environmental management and solving the problem of neighbourhood avoidance. At the beginning of the year, we started to monitor the electromagnetic radiation environment of 5G application base stations in major urban roads, logistics centres, residential areas and university gathering areas, etc. According to the analysis of the monitoring data, the electromagnetic radiation environment levels of 5G application base stations at various monitoring points in urban areas all meet the requirements of the Electromagnetic Environment Control Limits (GB8702-2014). With the development of 5G and the application of various scenarios, it is still necessary to continuously monitor the electromagnetic radiation environment in the future in order to grasp its changing trend.